2022
DOI: 10.1177/15346501221077703
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Exposure Therapy: A Case for Use With Refugees via Telehealth With the use of an Interpreter

Abstract: Rates of PTSD and depression are as high as or higher among samples of refugees than in the general population. There have been few randomized controlled trials of trauma-focused therapies conducted with refugees. Additionally, there has been little research on the use of interpreters in psychotherapy with refugees, but across the studies included in a meta-analysis, a nonsignificant difference between studies that used an interpreter and those that did not was found. Due to COVID-19, mental health providers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These low numbers are corroborated by studies assessing interpreter use and reporting the insufficient uptake, use of protocols and awareness of interpreter use in telehealth services. 27,[31][32][33] Although the low amount of interpreter uptake found in our study could have biased our association away from the null, our analysis adjusted this factor for potential confounders such as country of birth, socioeconomic disadvantage level and English use. It also aligns with other studies, 11,19,27 exposing the urgent need to address cultural and language barriers in telehealth design and use.…”
Section: Discussionmentioning
confidence: 93%
“…These low numbers are corroborated by studies assessing interpreter use and reporting the insufficient uptake, use of protocols and awareness of interpreter use in telehealth services. 27,[31][32][33] Although the low amount of interpreter uptake found in our study could have biased our association away from the null, our analysis adjusted this factor for potential confounders such as country of birth, socioeconomic disadvantage level and English use. It also aligns with other studies, 11,19,27 exposing the urgent need to address cultural and language barriers in telehealth design and use.…”
Section: Discussionmentioning
confidence: 93%
“…In general, studies have highlighted the ability to culturally adapt NET to meet the needs of diverse clients, though details on these adaptations are limited (Wright et al, 2020). Increasing exploration of the use of NET via telehealth has appeared promising (Olavarrieta & Benuto, 2022). However, in general, clinical research with TGNB youth has remained scant particularly in the context of the ongoing COVID-19 pandemic and challenges with accessing mental health services among TGNB individuals (Kidd et al, 2021).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…2021; Olavarrieta & Benuto, 2022). Moreover, outside of outcome data collected, there was limited information on additional supports and resources that were available during this time which may have impacted the clients' progress and maintenance of treatment gains following NET.…”
Section: Treatment Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this significantly reduced the barrier to attending sessions, it necessitates a careful navigation between the establishment of side relationships between the interpreter and client. Further, the ITA model may not be accessible in all settings, such as community clinics, due to financial or staffing considerations (Olavarrieta & Benuto, 2022; Woodward et al, 2020). However, it is noteworthy that clinical trials of NET with refugees have been found to be effective in both high and low resource settings (Cooper et al, 2019).…”
Section: Access and Barriers To Carementioning
confidence: 99%